Анализ атаки пассивного перехвата на пинг – понг протокол с полностью перепутанными парами кутритов - Василиу, Е. В.; Мамедов, Р. С. (Eastern-European Journal of Enterprise Technologies, 2009)
On the basis of methods of quantum information theory the eavesdropping attack with the use of auxiliary quantum systems on ping – pong protocol with completely entangled pair of three – dimensional quantum systems – qutrits is analyzed. The formula for quantity of the eavesdropper’s information as functions from probability of attack’s detection is deduced. It is shown, that the resistance against the attack of ping – pong protocol with pairs of qutrits is above the resistance of the protocol with pair of qubits